Immature teratoma of the posterior cranial fossa in a 4-month-old infant: A case report - GAO, JINXI (D.A. Spandidos, 2013)
The present study analyzed a case of immature teratoma in the posterior cranial fossa of an infant and compared the clinical data with the associated literature. Ventricular drainage was initially performed upon the patient’s admission to the hospital. Following adequate pre-operative preparations, the tumor in the posterior cranial fossa was resected on the third day. No significant neurological function deficiency was observed following the surgery and no recurrence was noted within an 18-month follow-up period. In such cases, treatment should be conducted in a stepwise manner, with the hydrocephalus relieved first, followed by complete tumor resection subsequent to full preparation. Post-operative chemotherapy was not performed by conventional means as the infant was too weak, therefore, periodic reviews and long-term follow-up were required.